Cultural maintenance and adaptation of different immigrant groups: Predictor variables. - Navas, Maria Soledad; López-Rodríguez, Lucía; Cuadrado, Isabel (Anales de Psicología / Annals of Psychology, 2013)
This study aimed to analyze the cultural maintenance and adaptation dimensions expressed by Moroccan, Romanian, and Ecuadorian immigrants in Spain, as well as psychosocial and social-demographic variables that predicted such tendencies. A correlational study was carried out with immigrants of Moroccan (N = 71), Romanian (N = 74), and Ecuadorian origin (N = 70) who responded to a questionnaire reporting their tendency to maintain the original culture, to adapt to the host culture, and their perceived duty to adapt to the host culture. It was also measured the stereotype dimensions of warmth and competence about Spanish people, out-group threat, in-group identification, perceived in-out-group similarity, nature of out-group contact, perception of inter-group relations, perceived enrichment by immigration, and some social-demographic variables. Results showed the importance of immigrants’ origin on all variables of the study. In addition, the predictors of acculturation dimensions were different depending on the group considered. These results highlight the need for specific interventions, as each immigrant group faces the adaptation process to the new host society in a different way.